Implementations of TACTO software for analysing athletic effects of parkour on youth football players' performance - Edriss, S (LASE Journal of Sport Science, 2019)
Improving social interactions, learning skills, health and confidence can be achieved through sport and motor development. Young athletes can adapt to new situations and learn various skills quicker than older athletes. The aim of the present study was to investigate the effect of parkour on youth football players' performance using Tacto software. Tacto software can evaluate players' motor skills in sporting environments. To conduct this study, 10 youth players of 8-10 years of age from the professional football club of Sheffield United Academy were selected. The players were asked to take part in 6 sessions of parkour practice. Their football performance was recorded using a 2D camera in indoor 5-a-side football matches prior to and during parkour sessions, and after the last parkour practice session. Tacto software was used to extract the players' performance parameters included velocity, displacement and acceleration from the recorded tapes. The performance parameters were analysed using SPSS and Excel. The results of paired t-test show significant differences in velocity, acceleration and displacement between football matches before parkour practice and after 6 sessions of parkour. Overall, football players' performance improved after they became familiar with parkour and it is anticipated that spending more time practicing parkour will result in the players' greater improvement and will ensure successful outcomes.